REALISTIC MATHEMATICS EDUCATION IN COOPERATIVE LEARNING VIEWED FROM LEARNING ACTIVITY - Ardiyani, Shila Majid; Gunarhadi, Gunarhadi; Riyadi, Riyadi (Journal on Mathematics Education, 2018)
This study aimed at searching the different effect of Student Teams Achievement Division (STAD) and Think Pair Share (TPS) types of cooperative learning models with Realistic Mathematics Education (RME) approach on the students’ learning outcome viewed from students’ learning activity. The observation, interview, questionnaires, and tests were used to obtain the data which were then analyzed using two-way ANOVA. The result of research showed that: (1) STAD with RME approach provides better learning outcome than TPS with RME approach does; (2) the students with high learning activities have mathematics learning outcome better than those with medium and low learning activities; and (3) there is no interaction between the model of teaching and learning activities students to the results of the students’  mathematics learning.